Exploring Character Dichotomy in Anna Todd's After Good Versus Bad - Weking, Mutiara Stefani Putri; Pramesti, Tri (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This research explores the dichotomy of characters in Anna Todd’s After through the lens of binary opposition as proposed by Lois Tyson and the deconstruction approach by Jacques Derrida. The study focuses on the clear demarcation between good and bad characters, epitomized by Tessa Young and Hardin Scott, respectively. Using Tyson’s framework, the binary oppositions within the narrative are identified and analyzed, revealing how these oppositions structure the reader’s understanding of the characters. Derrida’s deconstruction theory is then applied to challenge and destabilize these fixed oppositions, offering a nuanced interpretation of the characters’ complexities. The findings indicate that while Tessa Young is predominantly portrayed as the embodiment of goodness, and Hardin Scott as the epitome of badness, a deeper analysis reveals underlying complexities and contradictions in their characterizations. This study contributes to a richer understanding of character development and thematic depth in contemporary literature. However, through the application of Derrida's deconstruction, the research concludes that these binary oppositions are not absolute. The complex interplay between Tessa and Hardin challenges the rigidity of their characterizations, demonstrating that the boundaries between “good” and “bad” are fluid and subject to reinterpretation. Keywords: after, binary opposition, deconstruction, dichotomy, good and bad.